GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 523481798 species occurrences available in GBIF matching the query: TaxonKey: Quercus ilicifolia Wangenh. Year: >= 1980 HasCoordinate: true. The dataset includes 523481798 records from 12346 constituent datasets: 109 records from DAO Herbarium Type Specimens. 15 records from Urwald 2 (Bad Waldsee). 6 records from Boimstorfer Sundern. 93 records from Haarbach Höfe. 313 records from BIRDRACE Gätkes Erben. 91 records from BIRDRACE NABU LV Hessen. 936 records from Bats of Poland. 250 records from Aves MZS. 226 records from Himmelmoor. 220 records from Phthiraptera. 1702 records from BioGIS - Bryophytes - HUJ collections. 40565 records from Oregon State University Herpetological Collection. 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 373 records from Otter survey of Ireland 2004 & 2005. 1 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 74399 records from Marie-Victorin Herbarium (MT). 127 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 3509 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 27538 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 5534 records from Guadeloupe_Herbier. 26661 records from Plan de vertebrados de la Patagonia. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 1017 records from Irish Marine Turtle Database. 9636 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 53985 records from BioMar - LIFE project. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 991 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 54899 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 3633 records from Bioimages. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 480 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 11670 records from Naturalis Biodiversity Center (NL) - Crustacea. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 6 records from Hemichordata collection of National Museum of Nature and Science. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1 records from DMNH Eggs. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 378 records from Tsetse flies of East Africa update. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 139 records from The Bat Conservation Trust - Woodland Survey. 395 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 206 records from The Diptera Site. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 123309 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 119 records from Bryozoa of the British Isles. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 346 records from Mycological collection of the National Museum. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 9858 records from ISE - Herbário ISE. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 355 records from Herbier G. Garapin (BOUM). 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 10633 records from Biological Records Centre - Collembola Recording Scheme. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 10358 records from Census of the flora of Benin. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 61 records from University of Ghent - Zoology Museum - Vertebratacollectie. 2706 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 1485 records from IWDG Constant Effort Cetacean Sighting Scheme. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 11391 records from JOI - Herbário Joinvillea. 16 records from Siphonaptera. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 99300 records from Landesmuseum Kärnten. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 19 records from Revision von Suctobelba trigona (Michael, 1888). 2922 records from National Lesser Horseshoe Bat Database. 104 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 5709 records from Coleoptera of Piska Forest. 1292 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 8220329 records from OEH Atlas of NSW Wildlife. 1238 records from Insect Collection (CeStuBio). 21679 records from HUEM - Herbário da Universidade Estadual de Maringá. 8658 records from Mollusca collection of National Museum of Nature and Science. 3 records from MSB Mammal Observations (Arctos). 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 81429 records from African Rodentia. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 3509 records from Entocytheridae (Ostracoda) World Database. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 8934780 records from Botanical Society of the British Isles - Vascular Plants Database. 18 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 64603 records from HUFU - Herbarium Uberlandense. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 20 records from Truchas Mexicanas. 106428 records from Jordal. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 59016 records from Biological Records Centre - Isopoda (Interim dataset). 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 201409 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 191 records from Herpetofauna laguna El Tinije. 561 records from CSUC Vertebrate Collection. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 168884 records from Phanerogamic Botanical Collections (S). 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 228 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 510690 records from MVZ Herp Collection (Arctos). 3586 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 57492 records from PRECIS (KwaZulu-Natal Herbarium). 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 73327 records from University of Vienna, Institute for Botany - Herbarium WU. 9302 records from Ants from the Paraguayan dry Chaco. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1998 records from Aves de la cuenca media del río Bogotá. 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 5371 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 1168 records from Colección de Entomología - Diptera - Ceratopogonidae. 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 2438 records from Colección de peces dulceacuícolas de Costa Rica. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 833 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 89874 records from ecoscope_observation_database. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 1020709 records from Consortium of California Herbaria. 30872 records from Online Atlas of vascular plants 2012-2020. 4631 records from Southern Cape herbarium. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 310 records from WNMU Fish Collection (Arctos). 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 257 records from Colección nacional de palmas de Colombia - JBQ. 17 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 117692 records from Australian National Wildlife Collection provider for OZCAM. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 288 records from Fungi of Słowiński National Park, Poland. 353 records from Coastal and marine species. 2996 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 3 records from Reptilia Collection of Museum and Institute of Zoology PAS. 11638 records from Orthopteroidea. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 3091617 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 3076 records from dec2011. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4146 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 177466 records from CAS Entomology (ENT). 183 records from Collection entomologique Pierre Lachiver. 19555 records from KUBI Ornithology Tissue Collection. 3276 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 9809 records from UFG - Herbário da Universidade Federal de Goiás. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 11 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 443 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 47 records from Guyane_française_caféier. 38648 records from Marine species distributions in Irish coastal waters. 2700 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 433964 records from MVZ Mammal Collection (Arctos). 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 12065 records from Tromsø Museum, Bryophytes. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 34 records from New records in vascular plants alien to Kyrgyzstan. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 511 records from Coleoptera of Swierklaniec Forest. 12661 records from CCBER Herpetology Collection. 60670 records from QLD DERM Coastal Bird Atlas (Trial). 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 2546 records from The atlas of butterflies in Kraków. 3204 records from Faunal Inventory of Morysin Nature Reserve. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 356 records from Morphologische Daten von Puffinus creatopus. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 57845 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 24 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 6237 records from Plecoptera. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 1324 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 31 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 7 records from Order Diptera, family Mydidae. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 7892 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 19 records from Herbarium WRSL, Flora of the Silesia. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 825 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 5733 records from Small Mammal Research Database. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 45443 records from IAC - Herbário do Instituto Agronômico de Campinas. 8958 records from SANT-Lich. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 7421 records from Weevils of the Tatra Mts.. 551213 records from Bee Biology and Systematics Laboratory. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 29 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 48564 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 53815 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 2618 records from Portuguese Seaweeds. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 26141 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 1214311 records from AntWeb. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 1 records from Red list project inventory, bryophytes. 474 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 51 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 24268 records from Zoology (Museum of Evolution - Uppsala). 654 records from Helgeland Museum, Tabanidae. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 458185 records from Bird Atlas 2007 - 2011. 6335 records from Herbarium Vonderau - FULD. 226 records from Collection of Heteroptera. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 227 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 485 records from National Taiwan Ocean University. 1 records from Lissotes working-group. 39295 records from SPSF - Herbário Dom Bento José Pickel. 28315 records from SANT-Algae. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 212 records from Irish Federation of Sea Anglers Catch Data. 13863 records from Albany Museum. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 145959 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 899760 records from Naturalis Biodiversity Center (NL) - Botany. 1137 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 264 records from Entomological collection of the National Museum. 67 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 14 records from Type Specimen Database of Museum and Institute of Zoology PAS. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 125939 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 917964 records from PRECIS. 2494 records from Marine Environmental Monitoring - Marine Turtles. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 27670 records from CSIRO Ichthyology provider for OZCAM. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 1174 records from PReCAST Marine Mammal Sightings. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 1163 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 59792 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 623176 records from Fishbase. 94696 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 6541 records from Likona Invertebrates. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 28788 records from EPA River Biologists data. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 73408 records from SAIAB. 7693 records from NHM, Heteroptera. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 26104 records from SPF - Herbário da Universidade de São Paulo. 3 records from Collection Myriapoda - SNSD. 2513 records from Carabidae of the Tatra Mts.. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 3312 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 1526 records from University of Amsterdam (NL) - Páramo pollen reference collection. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 4415 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 1150 records from Paläontologie Marburg. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 1319 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 17618 records from BioGIS - Mammals - INPA database. 331 records from Guadeloupe_Bananier. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 49678 records from SANT herbarium vascular plants collection. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 3522 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 15 records from Projeto Abrace o Boto Cinza. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 190 records from Relative abundance of ostracods in sediment core Sv09. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 4826 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 1 records from Taxonomic review of the genus Wasmannia.. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 9349 records from Harriet Irving Botanical Gardens (HIBG). 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 4447 records from Lepidoptera (Observations). 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 44982 records from UFP - Herbário UFP - Geraldo Mariz. 154 records from Perot Museum of Nature and Science. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 61 records from Registros restauración ecológica- Magdalena medio. 31845 records from NPL collections. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 3978 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 165322 records from KUBI Mammalogy Collection. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 355 records from Colección de Entomología - Arthropoda. 349 records from Insect Collection from New Caledonia. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 3182 records from Finnish Entomological Database: Heteroptera. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 1024 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 599260 records from FLORIVON. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 2 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 35697 records from Sphaeroceridae Collection. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 17012 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 25 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 4 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 4311 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 77 records from Empria and Monsoma in Japan. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 2011 records from Local BioBlitz Challenge 2013. 4250 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 382 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 374 records from published_chenopodium_vulvaria_observations. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2107 records from MLZ Mammal Collection (Arctos). 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 75092 records from Herbario Universidad de Antioquia (HUA). 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 45718 records from Colección Herbario Federico Medem Bogotá - FMB. 4289 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 219 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 7671 records from HERBAM - Herbário da Amazônia Meridional. 29462 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 88290 records from URM - Herbário Pe. Camille Torrand. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 67708 records from University of Alberta Vascular Plant Herbarium (ALTA). 4 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 387501 records from Species data extracted from the National Vegetation Database. 10606 records from Cercle des mycologues de Montréal Fungarium (CMMF). 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 1854895 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 23334 records from Herbario Pontificia Universidad Javeriana. 102438 records from ICN - Herbário do Instituto de Ciências Naturais. 751 records from Trichoptera (caddisflies) of Ireland. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 834 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 1 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 24133 records from IICT Herbário LISC. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 618 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 1329 records from API_CRSN_Data. 19127 records from Biological Records Centre - Cerambycidae Dataset. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 4217 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 634166 records from Inventario Español de Especies Terrestres (MAGRAMA). 1 records from On centipedes (Chilopoda) of Albania, 2. 3 records from Note su alcune specie di chilopodi della regione palestinese. 368 records from Collection Crustacea - KAUMM. 6186 records from Chinese mitten crab (Eriocheir sinensis) occurrences in Flanders. 1690 records from Colección de Reptiles del Instituto Alexander von Humboldt. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 44 records from Solanum_baretiae. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 3257 records from fundiv france database. 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 253084 records from Lyman Entomological Museum (LEMQ). 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 6766 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 2557 records from Hosted Invertebrate Collection 01. 31 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 1 records from Herpetology. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 52 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 69797 records from Lepidoptera collection, Natural History Museum, University of Oslo. 9054 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 11839 records from Collection of Coleoptera. 52 records from Isotope tracer experiment: meiofauna counts. 5053399 records from Southern African Bird Atlas Project. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 956 records from National Museum of Marine Biology and Aquarium. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 4369 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 797 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3661250 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 59078 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 17802 records from The Bat Conservation Trust - Colony Count Survey. 75221 records from Hymenoptera specimen database of Kyushu University. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 63 records from (Data S1) Palynology of ODP Site 119-739. 14 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 73901 records from NCSM Fishes Collection. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 1826 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 12512 records from ULg_Hexapoda. 33521 records from Dragonfly Ireland. 23501 records from Amphibian Specimens. 80737 records from natagora-earlybirds. 363271 records from University of Florida Vertebrate Paleontology. 9879 records from Bibliographic records of Angola mammals. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 26624 records from Monitoring data from the federal state Bavaria (Germany). 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 5538 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 46 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 9127 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 1481 records from Reptilia notes, NTNU, Trondheim. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 253 records from UAFMC Birds. 2847 records from Kangawalla Bird Sightings. 13 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 1074 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 2880 records from Coleoptera, NEF. 1 records from Phytochorologie des départements français. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 2297 records from Joint Nature Conservation Committee - England Otter Survey Database. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 4855 records from University of Alberta Museums, Entomology Collection. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 2591 records from UAFMC Fish. 119366 records from The digitization of plant specimens of NTU. 1626459 records from SA Flora (BDBSA). 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 364 records from Colección Herpetológica de la Patagonia. 45 records from CHAS Vertebrates. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 224 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 1086 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 537 records from Ascomycetes of Russian Fennoscandia. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 20 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 17 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 11 records from Pollen profile from sediment core AV14_K2-4. 68 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 3956 records from SMDB - Santa Maria Departamento de Biologia. 455 records from Aschelminth collection of National Museum of Nature and Science. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 203672 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 355 records from Culture Collection of Cryophilic Algae. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 767 records from BioGIS - Bats - Asaf Tsoar database. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 755 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 582 records from Bioblitz 2013 Copenhagen Denmark. 58 records from Mamíferos laguna El Tinije. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 86556 records from NINA Vanndata øvrige arter. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 56095 records from Albany Museum Grant. 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 302790 records from BioFokus. 32 records from Fundación Miguel Lillo - Colección Invertebrados. 15570 records from Vertebrats d'Andorra. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 9112 records from UAM Fish Collection (Arctos). 32 records from Archaea Collection in BCRC. 2613 records from TTRS Ornithology. 917 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 201 records from BioAcoustica: Wildlife Sounds Database. 34 records from Sipuncula collection of National Museum of Nature and Science. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 6 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 313 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3688 records from Clare Biological Records Centre dataset. 443 records from The Fish Collection at the Zoologische Staatssammlung München. 49463 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 1559 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 71655 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 1 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 571 records from Collection of Hymenoptera. 895 records from Lichen.ie Data. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 70127 records from DMNS Bird Collection (Arctos). 5788 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 1364 records from Irish Collembola records. 12294 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 255 records from GENT Lactarius Deliciosi. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 136 records from Plants galls. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 4 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 588 records from Relative abundance of ostracods in sediment core Lz1120. 987 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 115 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 397 records from Danish Lacewings (Neuroptera). 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 109 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 52335 records from CESJ - Herbário Leopoldo Krieger. 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 48 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 146 records from Megophthalmidia_of_North_America. 27167 records from Bird tissue collection, Natural History Museum, University of Oslo. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 7410 records from Helgeland Museum, Lepidoptera. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 2357 records from MISE Project Otter Records, 2011-2015. 2 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 26566 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 15879 records from HAMAB - Herbário Amapaense. 151 records from Molluscan fauna of Gueishan Island of Taiwan. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 59493 records from Irish Vascular Plant Data - Paul Green. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 13716 records from OUPR - Herbário "Professor José Badini". 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 2126 records from HAS-Algae - Coleção Ficológica do HAS. 820550 records from Fauna Atlas N.T.. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 80 records from HSU Wildlife Eggs and Nests. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 7208 records from Royal Horticultural Society - Records from the RHS insect reference collection. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 3377 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 118357 records from NINA insect database. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 772 records from INRA-Versailles Arabidopsis natural variants. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 10052 records from CUMV Mammal Collection (Arctos). 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 52 records from CIM Specimens. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 133313 records from Field Museum of Natural History (Zoology) Bird Collection. 10254 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 29263 records from Tromsø Museum, Fungi. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 19 records from Counts of benthos communities in Kongsfjorden in 2009. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 87 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 22585 records from CUMV Fish Collection (Arctos). 94 records from LISU Herbario Angola. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 114472 records from UAM Mammal Collection (Arctos). 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 256 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 464 records from Lepidoptera collection, NTNU, Trondheim. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 378 records from CCBER Mammalogy Collection. 41438541 records from Artdata. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 3 records from Diatom abundance of Hole 38-338, Part 2. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 764 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 314 records from Peces laguna El Tinije. 48310 records from Museu Paraense Emilio Goeldi - Ictiology Collection. 99070 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 14371 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 3 records from MfN - Micropaleontology. 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 2334 records from Ohio University Invertebrate Paleontology Collection. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 9537 records from Herbier du Bénin. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 711 records from Odonata collection, NTNU, Trondheim. 2327 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 8579 records from The atlas of breeding birds in Małopolska. 461 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 1794 records from Flora of tanzania. 10923 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 18579 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 519290 records from Museum Victoria provider for OZCAM. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 2940 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 64882 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 20600 records from Butterflies of Ireland. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 32346 records from CRCM Vertebrate Collection. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 7 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 9088 records from Flora of Słowiński National Park, Poland. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 1754 records from Eggs Specimen. 71 records from (Data S1) Palynology of ODP Site 113-696. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 1905 records from BioGIS - Reptiles - INPA database. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 14587 records from Cowan Tetrapod Collection - Mammals. 268640 records from MBM - Herbário do Museu Botânico Municipal. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 228 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 1662 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 3 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 62015 records from Atlas of Iberian water beetles (ESACIB database). 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 1748 records from Harvestmen_of_French_Guiana. 2815 records from Helgeland Museum, Araneae. 5377 records from Herbario Museo de La Salle Bogotá (MLS). 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 8583 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 102 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 59 records from European bison in Białowieża Primary Forest. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 20 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 3720 records from Saproxylic Beetles of Ireland. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 10651 records from Danish Plant Bugs (Miridae). 21289 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 988 records from PSUZC-Amphibians Collection. 163444 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 2 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 119 records from Various insect orders, NEF. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 4128 records from Algae (S). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 11762 records from Chrysomelidae of the Carpathians. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 882299 records from SA Fauna (BDBSA). 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 7756 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 19633 records from Endemic plants of the Congo basin. 2 records from Collection Crustacea - ZSRO. 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 2 records from Araneae Collection. 2290 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 4926 records from Fungus herbarium, UiB. 170945 records from Field Museum of Natural History (Zoology) Mammal Collection. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 2 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 2913345 records from Especímenes INBio. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 3 records from Ichthyologie ZMK. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 201 records from MVZ Hildebrand Collection (Arctos). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 13 records from Ornithologie ZMK. 330 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 635514 records from Donnees ONF Faune-Flore-Fonge. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 805 records from HSU Wildlife Mammals. 146809 records from OHN. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 1129 records from Upper Silesian Museum, Insect Collection. 53587 records from Lund Museum of Zoology (MZLU). 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 10284 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 2 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 98873 records from CAS Invertebrate Zoology (IZ). 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 51 records from Packer Collection / Xenochilicola bees, Chile. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 25 records from Schwedische Oribatei (Acari). III.. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 1 records from Vermes ZMK. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 827 records from Colección Hidrobiológica del Chocó. 6518 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 10840 records from Bird skin collection, Natural History Museum, University of Oslo. 603 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 3221 records from Road Kill Survey. 5 records from Reptilia ZMK. 5842 records from FCAB - Herbário Friburguense. 3 records from Mammalogie ZMK. 15 records from Malakologie ZMK. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 10192 records from Crustacea collection of National Museum of Nature and Science. 496203 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 29 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 553 records from Crustacea ZMK. 27290 records from Bird Monitoring Data. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 1 records from Pantopoda SMF. 32109 records from Herbier de Nouvelle-Calédonie. 1 records from Cnidaria ZMK. 5 records from Echinodermata ZMK. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 16 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 982 records from Freshwater plants of Cameroon. 699357 records from Norwegian Biodiversity Information Centre - Other datasets. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 2 records from Collection Crustacea - PUM. 200 records from Zoological collection of the National Museum. 11491 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 1 records from On centipedes (Chilopoda) of Albania, 2. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 61 records from Shrews of Poland. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 9 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1561 records from Colección de Zoología Invertebrados - Otros invertebrados. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 8401 records from Herbarium areqvipense (HUSA). 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 261 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 3 records from New country records of reptiles from Laos. 83679 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 2077 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 749213 records from Historical Bird Atlas. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 1531 records from Culture Collection of Algae. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 24891 records from UAM Bird Collection (Arctos). 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 688 records from Algae, Norwegian College of Fishery Science. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 622 records from UCM Bird Eggs/Nests Collection (Arctos). 1003 records from NCSM PaleoBotany Collection. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 151 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 7 records from (Table 4) New palynological record of sediments from Odderade. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 30 records from Guadeloupe_Taro. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 2470 records from Annelida collection of National Museum of Nature and Science. 5581 records from IWDG Casual Cetacean Sightings. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1415 records from Plant observations from Białowieża National Park. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 12134 records from MPM Herpetology. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 3045 records from ESAS cetacean sightings from 1980 to 2003.. 832088 records from Museum of Comparative Zoology, Harvard University. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 4912 records from Herbier de Strasbourg. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 58050 records from Vascular Plant Herbarium, UiB. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 19695 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 4025 records from CCBER Ornithology Collection. 2 records from Neue Milbenarten aus Kärnten. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 7551636 records from BirdLife Australia, Birdata. 29 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 13 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 2954 records from Geneva Herbarium – Burnat Herbarium (G-BU). 1151 records from arim. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 4864532 records from Australia's Virtual Herbarium. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 4601 records from Invertebrate collection of University of Oulu Zoological Museum. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 36008 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 4328 records from Naturalis Biodiversity Center (NL) - Mammalia. 21742 records from Herbarium of the Université Libre de Bruxelles. 48 records from Tardigrada collection of National Museum of Nature and Science. 2091 records from Naturalis National Natural History Museum (NL) – Coelenterata. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 293298 records from SEAPOP NINA. 1667136 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 450 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 798 records from Biological Records Centre - Irish Otter Dataset. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 9948 records from Bees of Canada / Gschwendtner property collection. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 1509 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 17 records from Hazel Dormouse in Ireland. 49 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 12509 records from The Bat Conservation Trust - Hibernation Survey. 38650 records from Kathryn Kalmbach Herbarium. 6125 records from NMMNH Mammal. 73341 records from Ichthyology Collection - Royal Ontario Museum. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 1696 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 9775 records from Finnish Entomological Database: Hymenoptera. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 69 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 606 records from Líquens d'Andorra. 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 152552 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 6004 records from Colección Limnológica Universidad de Antioquia. 67350 records from CAS Ornithology (ORN). 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 4852551 records from Bird Ringing Centre in Sweden (NRM). 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 163 records from Entomofauna laguna El Tinije. 260950 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 39267 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1588 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 6933 records from Natural History Museum Maastricht (NL) - Herbarium. 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 153532168 records from EOD - eBird Observation Dataset. 1474161 records from Consortium of California Herbaria. 579 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 1 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 29 records from Colección Nacional de Heliconias. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 27334 records from Kyushu University Museum Coleoptera Collection. 49637 records from Monitoring data from the federal state Hesse (Germany). 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 26236 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 642 records from Reunion_Coffea. 7598 records from National Taiwan University. 3669 records from ARKO strandeng. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 135 records from UCM Vertebrate Observations Collection (Arctos). 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 732640 records from iNaturalist research-grade observations. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 1589 records from Aquatic Oligochaeta of Ireland. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 25204 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 34 records from National System of Protected Areas in Poland - Fungi. 3002 records from Colección de Peces Universidad Católica de Oriente. 828 records from UCBG TAPIR Provider. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 152790 records from CONN. 66 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 63267 records from Recent Invertebrates Specimens. 5578 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 1077 records from BioGIS - Fish - HUJ collections. 6 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 64 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 304689 records from Aranzadi Ringing Scheme (bird ring-recovery data). 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 19634 records from H.A. Stephens Herbarium. 250 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 4627 records from Coleção de Polychaeta do Museu Nacional. 110017 records from Louisiana State University Herbarium - Vascular Plants. 2 records from A new ant genus from the southwestern United States.. 4 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 9818 records from NYSM Birds. 28 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 19464 records from Hemipteran specimens of Iwate Prefectural Museum. 360 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 8518 records from Upper Silesian Museum, Bird Observations. 1072 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 309 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 2 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 1313 records from Birds collection of Abiko City Museum of Birds. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 1789 records from Birds collection of Yamashina Institute for Ornithology. 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 1712 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 50000 records from observe_tuna_bycatch_ecoscope. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 1572 records from Fongs d'Andorra. 10866 records from Heteroptera of Ireland. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 470 records from Spiders_of_French_Guiana. 2882 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 21188 records from National Bat Database of Ireland. 33 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 33 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 92 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 55 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 2275 records from UFRN-Fungos - Herbário UFRN - Fungos. 21868 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 10050 records from KUBI Ichthyology Tissue Collection. 6 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 181 records from Alien Species in Poland - Animals. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 492 records from Flora of Japan Specimen Database. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 8390 records from University of Lethbridge Herbarium (LEA). 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 17 records from Musée Vert ornithology collection. 111886 records from Invertebrates Collection of the Swedish Museum of Natural History. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 83546 records from UCJEPS TAPIR Provider. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 1900 records from Fungi Collection. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 33173 records from Global Lacustrine Diatoms. 11 records from Pollen profile from sediment core AV14_K2-1. 1035 records from National Museum Of Marine Science & Technology. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 3330 records from Herbier A. Le Grand (BOUM). 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1727 records from Herbier National de Mauritanie (HNM). 2966 records from Bolivian Amazon lowland fish metacommunity data. 31259 records from SABCA. 8706 records from NINA botanical collection. 98 records from Macrophytes_CLF. 419514 records from Meadow and Pasture Inventory (SJV). 23386 records from NCSM Vertebrate Paleontology Collection. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 40 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2477 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 25883 records from Monitoring data from the federal state Saxony (Germany). 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 537 records from The French National Collection of forage and turf species (grasses and legumes).. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 18056 records from University of California Museum of Paleontology. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 1447 records from Odonata of the Congo River 2010 expedition. 5787 records from HUSC - Herbário Unisanta. 1265 records from Actinomycetes Collection in BCRC. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 258 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 42004 records from Mammals housed at MHNG, Geneva. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 243739 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 106011 records from mel. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 1474 records from Herbarium Rhoenmuseum Fladungen. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 353 records from DMNS Marine Invertebrate Collection (Arctos). 84521 records from BioGIS - Vascular plants - INPA database. 3629 records from Wildbook for Whale Sharks. 9678 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 73166 records from ALCB - Herbário Alexandre Leal Costa. 23803 records from rmca-albertine-rift-butterflies. 32002 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 1244 records from Mosquitoes_of_French_Guiana. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 152495 records from Essig Museum of Entomology. 174490 records from CAS Ichthyology (ICH). 21 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 8097 records from HPBR - Herbário Padre Balduino Rambo. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 8441 records from Natural England - Batsites inventory for England. 23215 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 613 records from Countryside Council for Wales - Shad Monitoring data. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 39 records from ECOCEAN MantaMatcher. 3 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 196 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 18004 records from Census of the animals of Benin. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 7 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 1117 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 2013319 records from NMNH occurrence DwC-A. 7491 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 3820 records from Collection entomologique Barthélémy. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 1838 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 1340 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 3327 records from BioGIS - Mammals - SPNI. 24819 records from DMNS Mammal Collection (Arctos). 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 17447 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 1658 records from MISE Project Waterford Otter Records, 2011-2015. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 111 records from Birdrace-Uhulogen-Lippe. 252060 records from Moths Ireland. 1552 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 46360 records from TNHC Ichthyology Collection. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 18847 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 109 records from Birdrace-Team_Charadrius-Günzburg. 108 records from Birdrace-TriumVIErat-Viersen. 85 records from Birdrace-Die_Paradiesvögel-Herford. 76 records from Birdrace-Birding_for_Nature-Bonn. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 185 records from Klasse 3a. 241 records from BIRDRACE RennVögel Münsterland. 162 records from Siegen/ Gymnasium Am Löhrtor. 128 records from Birdrace-Brut-Wetteraukreis. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 120 records from Birdrace-Kosmos_Racer-Freising. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 951 records from Literature based species occurrence data of birds of North-East India. 112 records from Birdrace_Die_Borner-Viersen. 105 records from Birdrace-ARKONAuten-Rügen. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 110 records from Birdrace-LiLaMai-Vechta. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 263 records from Artenvielfalt Kreis Gießen. 114 records from Birdrace-Finkenspötter-München. 88 records from Birdrace-WeserEggeLäufer-Höxter. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 59 records from Im Bauerngarten. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 257 records from Seewasen. 271 records from Beweidungsprojekt an der Nesse. 122 records from Kloster Eberbach. 52 records from Fledermaus. 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 57 records from Waldhusener Moor (Lübeck-Kücknitz). 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 101 records from Birdrace-Herford-Birder-Herford. 100 records from Birdrace-Meister_der_Herzen-Kleve. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 95 records from Birdrace-Buteo1_DO-Dortmund. 92 records from Birdrace-Team_BO-bachter-Bochum. 103 records from Birdrace-Die_Nachtigallen-Herford. 72 records from Birdrace-Buteo2DO-Dortmund. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 96 records from Birdrace-federleser-Herford. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 91 records from Birdrace-Enger_am_Spektiv-Herford. 127 records from Birdrace_Schräge_Vögel-Herford. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 360 records from Küstenschutzwald. 37 records from Berlin - Treptower Park / Karpfenteich. 426 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from Borkhart. 198 records from FNL e.V.. 83 records from Spechtwald. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 80 records from Förderzentrum Schmölln. 70 records from Lech 2001. 151 records from Isarufer. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 114 records from Flora. 100 records from Feriendorf Ober-Seemen. 97 records from LauWi. 144 records from Ehmkendorf. 100 records from Grenzturm Hohen Neuendorf. 145 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 342 records from Kremmer Luch. 44 records from "Schlechteberg" Ebersbach/Sa.. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 97 records from Döchtbühlwald (Bad Waldsee). 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 6443 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 113 records from Hochschulgelände (Bremen). 57 records from Heidesee / Halle. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 101 records from Naturgrundstück (Eutin). 245 records from Kiesgruben Wemb. 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 233 records from Föhrenried (Fronreute und Baindt). 270 records from Regenrückhaltebecken (Zeulenroda). 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 55 records from Waldsee. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 69 records from Lassentiner Moor (Niepars). 84 records from Roter Berg Werdau (Leubnitz). 69 records from Schulgarten mit Klasse 8a (Essen). 15 records from AKG-Bensheim. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 66 records from Wedeler Au. 282 records from Deponie Klausdorf. 23 records from Alter Nördlicher Friedhof (München). 20 records from Motzener Tonsee. 313 records from Stadtpark Herzberg (Elster). 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 167 records from Zielbach (Töll). 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 170 records from Bodenseeufer Radolfzell. 150 records from Steinbruch Mainz-Weisenau. 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 325 records from Triebesbach (Zeulenroda-Triebes). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 56 records from Zitadelle Berlin-Spandau (7b). 46 records from Hainbachtal in Oelsnitz/V.. 101 records from Naturhausgarten. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 107 records from Landschaftsschutzgebiet Buchhorst 3. 124 records from Wiesenbiotop am Wasserturm. 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 39 records from Südpark (Bochum-Wattenscheid). 45 records from Flusswerder in der Weser (Hameln). 31 records from Nationalpark Harz Schul-AG Braunlage. 85 records from Insektenvielfalt Ahe/Weichelsee. 106 records from Schulgarten Hans-Carossa-Oberschule. 122 records from Stever. 32 records from Schulhof Sandhofenschule (Mannheim). 163 records from Brander Wald (Stolberg). 103 records from Wasserwerkspark (Chemnitz). 103 records from Schwanseepark (87645 Schwangau). 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 64 records from Kabelskebach (Kabelsketal, Saalkreis). 54 records from Wiese am Unterbecken. 95 records from Ortelsbruch - Hangmoor bei Morbach. 69 records from "Schwarzes Teich" (Waldpark Radebeul). 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 62650 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 86 records from Alter Kreidebruch Saßnitz/Rügen. 161 records from Schussenaue bei Berg. 22 records from Dellwiger Bach (Dortmund). 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 41 records from Örtzemündung (Stedden). 308 records from Wangerooge. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 96 records from Die Wuhle. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 219 records from Umgebung der Grundschule Oderberg. 149 records from Wirbach. 145 records from privater Garten. 79 records from GymnQuerfurt. 108 records from Mainufer. 212 records from Artenvielfalt im Beckerbruch (Dessau). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 180 records from Paul-Gerhardt-Schule Dassel. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 113 records from Rund um das LUGY. 71 records from Bolzplatz. 18 records from Spielwiese. 18 records from Mittelstreifen. 59 records from Rund ums Ökohaus (Würzburg). 50 records from Junge Heide, Radebeul/Dresden. 54 records from Ludwigshofen. 9 records from Willersalpe. 54 records from Zentralfriedhof (Wien). 63 records from Erft in Selikum (Neuss). 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 73 records from Varnhalt. 79 records from Balkon (Norderstedt). 12 records from Kindergarten. 117 records from Wassermann. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 181 records from Spießwoogtal / Königsbruch (Fischbach). 99 records from Düne am Ulvenberg (Darmstadt). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 61 records from Artenvielfalt auf der Wiese. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 35 records from Urwald 3 (Bad Waldsee). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 110 records from Obstwiese Osterberg. 28 records from Sandgrube Zaisertshofen. 111 records from Ökologischer Weinberg (Guntersblum). 48 records from Trockenrasen bei Dörndorf. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 77 records from Trockenrasen Franzigmark (Halle/Saale). 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 41 records from Wiese und Bach beim Unterbecken (Markersbach). 99 records from Dorfrand Mauderode. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 160 records from Wirbach-Taubental (Bad Blankenburg). 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 65 records from Mauernacker (Wettsaasen). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 98 records from Warnowtal (Rostock). 139 records from NSG Leist bei Ziegenhain. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 101 records from Isartal Dingolfing. 147 records from NABU-Auerochsenweide. 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 17 records from Schutzgebiet Ochtersum. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 43 records from Saalewiesen Naumburg. 53 records from Weidegut Rechab. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 107 records from vegoek. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 5 records from Streuobstwiese (Mittelgasse 4). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 22 records from Heilpflanzen im Hainbachtal. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 28 records from Uferzone Wipper (Biesenrode). 22 records from Breitkopfbecken (Berlin-Reinickendorf). 62 records from Amtsrain Apolda-Zottelstedt. 193 records from Gelände des Schulzentrums am Himmelsbarg. 59 records from Oschenberg, NO von Bayreuth-Laineck. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 153 records from Selztal bei Friesenheim. 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 1 records from Revision of the Nearctic endemic Formica pallidefulva group.. 40 records from Flächennaturdenkmal Grubditz. 245 records from Gieselbachtal Fulda-Harmerz. 50 records from Artensuche auf den Elbwiesen in Radebeul. 4 records from Schulbiotop und Brigach (Villingen). 19 records from Goethe-Hauptschule/Projekt I-10. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 43 records from Schulgelände Thurmair-Gymnasium. 55 records from Flora und Fauna am Mittelrheintal. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 95 records from Vielfalt verschiedener Wiesen. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 58 records from Weidewirtschaft. 92 records from Birkenloh. 783 records from Moluscos Marinhos de Augusto Nobre. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 28 records from Hainbachtal bei Oelsnitz / V.. 214 records from Binsenwiesen. 155 records from Bammentaler Duft- und Heilkräutergarten. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 207 records from Biosphäre Bliesgau. 40 records from Öhmdwiesen und Göldern (Konstanz). 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 60 records from Schafsweide Seniorenhaus Berghof. 244 records from WildesMoor bei Schwabstedt. 94 records from Kochertgraben II. 172 records from Dalbekschlucht. 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 63 records from Hochschule Zittau/Görlitz. 98 records from Rund ums Cani. 93 records from Höltigbaum. 10 records from Feuchtwiesen Wippertal bei Wippra. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 47 records from Neanderthal. 86 records from Naturerlebnisraum Koppelsberg (Plön). 15 records from Regenwasserabfangsbecken (Erlenbach). 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 60 records from NABUGEO1. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 134 records from Birdrace-Team_Havelland-Havelland. 155 records from Birdrace-Usedommeln-Ostvorpommern. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 61 records from GE-Brühl. 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 69 records from Entdeckertour am Muldestausee 1/05. 54 records from Weidegebiete in der Selzrenaturierung. 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 39 records from Soolbach-Tal. 128 records from Birdrace_turbine_untersee-Konstanz. 89 records from Birdrace-Team_Wangerooge-Friesland. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 53 records from Bad Bodenteicher Heide. 31 records from Kurler Busch (Scharnhorst). 36 records from Selz (Ingelheim am Rhein). 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 172 records from Leben im Finkensteiner Moor. 133 records from Wulfsmuehle/Pinnau. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 122 records from Birdrace-Hügelland-Mainz/Bingen. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 39 records from Stausee Weiditz. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 23 records from Wiese Niederaula. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 97 records from Landschaftspark St.Leonhard-Deisendorf. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 100 records from Birdrace-The_Ringers-Friesland. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 96 records from Birdrace-Berlin_Sparrows-Uckermark. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 79 records from Birdrace-Bielefinken-Bielefeld. 42 records from sbosch. 4 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 57 records from Schulgarten Fichteschule. 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 62 records from Zoo Frankfurt. 102 records from Industriebrache (Kempen). 13 records from Garten Hamburg Uhlenhorst. 142 records from Kinderbauernhof Pinke-Panke. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 15 records from Die geheimnisvolle Welt der Spinnen. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 22 records from Bachabschnitt der Nette (Osnabrück). 24 records from Kaisertal. 15 records from Beisetal bei Niederbeisheim. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 24894 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 63 records from Sternwiese Mülheim-Broich. 71 records from Birdrace-do_elster_Dortmund. 29 records from Naturerfahrung. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 65 records from LSG "Großes Bruch". 41 records from Morphologische Daten von Natrix. 46 records from 8c. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 21 records from Riedkanal Bötzingen. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 81 records from Birdrace-Die_Ornithomaten-Herford. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 78 records from Birdrace-Die_Laufenten-Braunschweig. 20 records from Lerchenauer Baggersee (München). 21 records from Bach. 221 records from Römertal (Steinpleis). 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 51 records from Steinbachtal (Würzburg). 81 records from Stadtpark Schmölln. 87 records from Klütwald. 40 records from Schulhof Liebfrauenschule Oldenburg. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 49 records from Dörnberg. 31 records from Regenwasserabfangbecken. 64 records from Schafheide im Böblinger Wald. 10 records from Ökowerk Emden. 21 records from Tauchen und Meer 02. 84 records from Streuobstwiese Haus Zeitz. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 36 records from Plöwener Wald. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 47 records from Schulgelände Ceciliengymnasium. 54 records from Park Schönfeld (Kassel). 26 records from Erhard Sopp. 27 records from Vögel. 68 records from Streuobstwiese. 23 records from Ackerrain Plönhagen. 57 records from Garten in Schmölln. 51 records from Schrebergarten Düsseldorf Oberkassel. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 39 records from Regenrückhaltebecken Bad Bevensen. 117 records from Naturschutzgebiet Kochertgraben. 13 records from Tiere im Teichgebiet. 11 records from Waldgebiet Todtnau- Sonnhalde. 81 records from Schulgarten-St.-Georg-Gymnasium. 23 records from AKG-Gelände in Bensheim. 4419 records from MVZ Bird Observations (Arctos). 64 records from Pilzlehrwald. 35 records from Gym Freyung. 101 records from Hoher Stein Kallenhardt. 51 records from Mühlenbach bei Buxtehude. 141 records from Draubiotop Lavamünd. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 56 records from Estetal (Buxtehude). 29 records from Brenz (Heidenheim). 19 records from Glemstal (Leonberg). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 22 records from Kaltenkirchen Brache. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 57 records from Mauervegetation,Flechten und anderes. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 26 records from Schulteich Heinrich-Mann-Schule. 27 records from Zwickau- Schwanenteich. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 24 records from Ornithologische Wanderung um Tussenhausen. 64 records from Issumer Fleuth. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 32 records from Nationalpark Harz Juniorranger. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1174 records from Sudeniederung (Amt Neuhaus). 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 36 records from Olympiapark (München). 48 records from Heider Bergsee (Brühl). 10 records from schlittschuhweiher. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 27 records from Wiese hinter der Schule (Darmstadt). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 23 records from Tümpel Schulbiologiezentrum. 28 records from Stadtpark Prinzengarten (Sigmaringen). 16 records from Upper Silesian Museum, Bird Collection. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 29 records from Insekten. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 17 records from Kohlbach (Sulzfeld). 18 records from Naturtag. 15 records from Kirchheller Heide ( Bottrop). 12 records from Ohemoor (Hamburg/Norderstedt). 80 records from Lahnufer in Villmar. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 13 records from FND "Weißer Berg" Leißling. 3 records from FFR Hausen. 9 records from Wiesendreieck Luckenwalde. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 8 records from Kleiner Ziergarten Winzingen (Neustadt). 20 records from Mikroorganismen. 15 records from Bodentiere rund um die Schule. 36 records from Salzwiese Diekskiel. 719 records from IBF Monitoring of Plant Galls. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 5 records from Feuchtwiese. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 34 records from Wattenmeer-Safari (Wurster Watt). 27 records from Bäche im Mooswald (Vörstetten). 12 records from Kinderwald Hannover. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 45 records from Georgs-Padd (Wangerooge). 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 13 records from Warnowufer Groß Klein. 1 records from Graureiher in Lans. 6 records from Fließgewässeruntersuchung am Haselbach. 16 records from Im und um das Schulhaus. 8 records from Krittenhorster Wald (Ostkilver). 23 records from Wattuntersuchung (Cuxhaven). 17 records from Tierpark Zittau. 21 records from LBV-Kindergruppen Markt Tussenhausen. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 6 records from Sächsische Schweiz (Pfaffenstein). 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 11 records from Privatteich(St.Leon). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 10 records from Bachpatenschaft Beeke. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 7 records from Stadtrandlandschaft Apolda-Nord. 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 40 records from Tiere und Pflanzen um uns herum !. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 24 records from Tauchen und Meer. 4 records from Sächsische Schweiz (Wehlener Gebiet). 15 records from Tiere. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 94 records from Landschaftsschutzgebiet Buchhorst 4. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 1 records from Waldtag in und um Seelingstädt. 4 records from Neues Testprojekt. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 91331 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 1114 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 169 records from Expedition "Schulgelände". 59 records from Schulteich Freie Waldorfschule Darmstadt. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 5 records from Schulinnenhöfe (Gelsenkirchen). 12 records from Schulgelände Erich-Kästner-Schule. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 135 records from Waldi-Weiher. 3 records from Blankenfelder See. 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from 5. Wiener Gemeindebezirk. 5 records from Fledermäuse u. nachtaktive Insekten. 1 records from Fledermäuse über der Alster (Hamburg). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 80 records from Landschaftsschutzgebiet Schmutterwald. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 2 records from Hildener Heide - Spörkelnbruch (Haan). 1 records from Karpfenteich, Klasse 6d. 555 records from FFH-Gebiet "Calwer Heckengäu". 371 records from Bannwald Burghauser Forst. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 107 records from Müritz-Nationalpark. 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 13 records from Tag der Artenvielfalt am Bruckenwasen. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 61 records from Fürstenberger Ralley Teil 3. 359 records from Pöhlberg bei Annaberg. 89 records from Schulgelände Paul-Gerhardt-Schule. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 366 records from Weinberg Reichersdorf. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 15 records from Kühnauer Aue und Kühnauer See. 52 records from Naturschutzstation Weinberghaus (Dessau). 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 145 records from BIRDRACE Dith Marsh Sandpiper. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 1177 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 146 records from LK 11 im Mönchspark. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 126 records from Schulwald Marksuhl. 517 records from Schulzentrum "Parc Hosingen". 274 records from Bernhardsthal. 369 records from BIRDRACE Havelland. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 254 records from BIRDRACE Thüringer Becken-Birders. 138 records from BIRDRACE Arkonauten. 258 records from BIRDRACE Raumpatrouille Oriolus. 65 records from BIRDRACE Federal Birds of Investigation FBI. 140 records from BIRDRACE Guckers Offenbach. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 157 records from BIRDRACE Rheinische Wasserrallen. 80 records from BIRDRACE Falkenberger Fluppis. 84 records from BIRDRACE Avinauten. 91 records from BIRDRACE SchrägeVögel. 95 records from BIRDRACE accipiter hardcore birding. 100 records from BIRDRACE Stuttgart 100 trööt. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 74 records from Schulwald Grundschule Brügge. 161 records from BIRDRACE Nord-Seh-Team. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 269 records from BIRDRACE Kosmos-Racer. 69 records from BIRDRACE Pfeifenten. 95 records from BIRDRACE BiBi. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 144 records from BIRDRACE Die Mohrenlerchen. 272 records from BIRDRACE Niederlausitz-Team. 279 records from BIRDRACE Wannacks Topti(c)ker. 287 records from BIRDRACE Pody und Co. 274 records from BIRDRACE Asiola-Quartett. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 118 records from BIRDRACE Die Lippegeier. 78 records from BIRDRACE leucorhö statt logorrhö. 278 records from BIRDRACE Usedommeln. 139 records from BIRDRACE Turbine Untersee. 256 records from BIRDRACE Upupa epöpse. 82 records from BIRDRACE Buteo2DO. 96 records from BIRDRACE OAG Neuwerk. 96 records from BIRDRACE Emslandracer. 101 records from BIRDRACE Enger am Spektiv. 102 records from BIRDRACE Willi goes Birding. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 106 records from BIRDRACE Ave Goettingen!. 131 records from BIRDRACE Brut. 119 records from BIRDRACE Tick, Trick und Track. 54 records from Königsdorfer Wald. 73 records from VFD-HH/SH: Pferdweide Lammert. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 82 records from BIRDRACE Die Ziegeneier. 84 records from BIRDRACE Bielefinken. 103 records from BIRDRACE Die Otzberger. 104 records from BIRDRACE Erlanger Piepmätzchen. 79179 records from All Ireland Non-Marine Molluscan Database. 105 records from BIRDRACE coesfelder_vogelkundler. 126 records from BIRDRACE Duckehühnchen. 120 records from BIRDRACE The early birds. 66 records from Langes Tannen(LMS), Klasse 5d. 166 records from BIRDRACE Die Düsselmöwen. 97 records from BIRDRACE NABUhu Trier!. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 102 records from BIRDRACE Buteo1DO. 98 records from BIRDRACE Die Paradiesvögel. 99 records from BIRDRACE TEAM BO-BACHTER. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 102 records from BIRDRACE Westfälische Nachtigallen. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 103 records from BIRDRACE federleser. 105 records from BIRDRACE Kiesmätze. 174 records from BIRDRACE Bon(n)apartemöwen. 149 records from BIRDRACE Birding Bentheim. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 134 records from BIRDRACE Griffin Wood Warblers. 132 records from BIRDRACE Die Wetterauer. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 115 records from BIRDRACE Die UHULOGEN. 114 records from BIRDRACE VIE will rock you!. 111 records from BIRDRACE Die Wendehälse. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 114 records from BIRDRACE Di-Bi-Di-Birder. 109 records from BIRDRACE Die Borner. 107 records from BIRDRACE Herford Birders. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 402 records from Tag der Artenvielfalt in Heidelberg. 2214 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 60102 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 112 records from BIRDRACE Hügelland zu Fuß. 110 records from BIRDRACE Angeliter Ornis. 121 records from BIRDRACE Immerwiederhopf. 44 records from Wiesen am Treffpunkt Freizeit. 37 records from Liether Park 2 (LMS), Klasse 6c. 144 records from Lustbach-Umland. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 113 records from Tornoer Teich. 99 records from Streuobstwiese Stedar. 194 records from Bodenteicher Seewiesen. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 61 records from Wälder im Hainbachtal. 83 records from BIRDRACE Die Frankenpfeifer. 112 records from BIRDRACE Gütersloher Gimpel. 107 records from BIRDRACE Borussia Zippammer. 62 records from Hettstadt Gehäge. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 54 records from VFD-H: MIttelgebirgsweide. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 120 records from BIRDRACE Die TUErteltauben. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 108 records from BIRDRACE Diesmal sehen wir mehr. 67 records from Tongrube bei Hettstedt. 173 records from FFH-Gebiet Klosterwasser/Burkau. 145 records from Gronau - auf der Suche nach dem Neunauge. 504 records from Schatzinsel Wangerooge. 121 records from Owere Fiddel. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 54 records from Biotope im Schulumfeld. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 269 records from BIRDRACE speedbirder. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 277 records from Colección de Entomología - Auchenorrhyncha. 114 records from Liether Kalkgrube. 62 records from Lebensraum Dorf. 116 records from Sürther Aue. 80 records from Feldweg Waldkirchen. 132 records from Aachtobel. 101 records from Steinbruch Kronungen. 85 records from Rund um den Hainbergsee. 54 records from Wir erkunden die Hofau, Klasse 5c. 29 records from Waldwiese. 248 records from Schulgarten der Volksschule. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 85 records from Ober-Olmer Wald. 96 records from "Ahrschleife bei Altenahr". 214 records from Pflanzen und Tiere im Burgwald. 36 records from Liether Park 1 (LMS), Klasse 5b. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 66 records from Von der Nutzung zur Natur. 49 records from VFD-H.: Rheingau: Bärstadt. 269 records from BIRDRACE Dithmarscher Deichhühner. 61 records from BIRDRACE Baumläufer. 76 records from BIRDRACE Nachtigallen. 84 records from BIRDRACE Birding for Nature. 88 records from BIRDRACE Kingfisher. 177 records from BIRDRACE Mehr Seh Team. 176 records from BIRDRACE Professorenteam. 110 records from BIRDRACE Linumer Luchschleicher. 79 records from BIRDRACE Blinde Hühner. 143 records from BIRDRACE Die Laufenten. 90 records from BIRDRACE TicTacToe. 106 records from BIRDRACE Die Schwenker-Birder. 104 records from BIRDRACE Andechser Stativträger. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 101 records from IBF Monitoring of Orthoptera. 114 records from BIRDRACE LiLaLau. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 69 records from Unter hellen Zinnen und finsteren Grotten. 101 records from BIRDRACE nabu-rhein-main.de. 102 records from BIRDRACE Niederrheinische Bartgeier. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 120 records from BIRDRACE Ornis im Einsatz. 18 records from Landschaftsschutzgebiet Buchhorst2. 69 records from BIRDRACE Mathilden-Käuze. 2070 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 84 records from BIRDRACE Vogelscheuchen. 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 31 records from Düpenauwiesen. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 40 records from BUND Naturschutzzentrum St. Julian. 146 records from BIRDRACE VdW Wilder Westen. 18 records from Schulgarten der Gesamtschule Am Heidberg. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 27 records from Schulgarten Waldorfschule Hassfurt. 94 records from FFH-Gebiet Paartal. 47 records from Schulgelände Grolland. 88 records from BIRDRACE Vogelkucker. 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 5739 records from NX - Herbário Nova Xavantina. 38 records from Was lebt in der Brutzwiese?. 57 records from Schulgarten Janusz-Korczak-Realschule. 30 records from Geführte Wanderung im Eselsbachtal. 75 records from BIRDRACE Die Kartoffelsäcke. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 6325 records from Colección Entomológica de la Universidad de Antioquia. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 63 records from Rosarium (LMS), Klasse 6a. 45 records from Reusaer Wald. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 12 records from Art´n Vielfalt im Kinderwald. 58 records from Schulgarten Zinnowwald-GS. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 17 records from Bachrenaturierung Littfe. 48 records from Wahner Heide LK 12 Biologie. 52 records from Aktion der Klasse H2 in Simmelsberg. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 7938 records from European riparian ground beetles. 12 records from Flora und Fauna am Mühlberg. 59 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >125 µm. 53 records from BIRDRACE Taubenhaucher. 152 records from BIRDRACE NAJU-Aspach. 99 records from VFD HH/SH "Pferdeweide Lemsahl". 33 records from Schüler erforschen die Helme-Aue. 30 records from Leben auf einer Sturmfläche. 77 records from VFD-RP: Taunus: Mähweide Dehe. 1 records from Streuobstwiese Alt Necheln. 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 930 records from Benthic foraminifera counts of sediment core PS2644-5. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 7 records from Die Bachspezies. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 30 records from Riekdahler Wiesen. 17 records from Nachtinsekten am Muldenufer. 30 records from Höhle am Neuweg / Sächsische Schweiz. 51 records from Kindervilla Außengelände. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 61 records from (Table 1) Sedimentology of core D11957P. 5477 records from Colección de mamíferos de la Universidad del Valle. 192 records from "Schwarzwassertal" bei Pobershau. 259 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 31 records from Benthic foraminifera counts of sediment core PS2644-2. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 1385 records from NRM-Herpetology. 117 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >125 µm. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 108 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 85 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, >125 µm fraction. 18 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, >125 µm fraction. 75 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 96 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 10 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 30-63 µm fraction. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, >125 µm fraction. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 214 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-43. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 114 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-52. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 45 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-09. 41 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 273 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core GIK17728-1 (Table 4). 349 records from Benthic foraminiferal assemblage in the 125-250 micron fraction of sediment core PS1745-5 (Table 5). 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 212 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 33 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, 63-125 µm fraction. 50 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 837 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 124 records from Benthic foraminifera assemblage in sediment core BBLL3_MC2. 2 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 5110 records from Live benthic foraminifera in South Atlantic surface sediments. 335 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 545 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 169 records from Benthic foraminifera assemblage in sediment core BBLL2_MC1. 128 records from Benthic foraminifera assemblage in sediment core BBLL2_MC4. 945 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23414-9 in the Norwegian Sea. 733 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 13 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 30-63 µm fraction. 48 records from Assemblage of living benthic foraminifera in sediment profile GeoB4901-6. 216 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 69 records from Review of the genus Namadytes Hesse, 1969 (Insecta: Diptera: Mydidae: Syllegomydinae). 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 684 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 108 records from Assemblage of living benthic foraminifera in sediment profile GeoB4906-5. 145 records from Assemblage of living benthic foraminifera in sediment profile GeoB4909-4. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 998 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23414-9 in the Norwegian Sea. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 663 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 432 records from Benthic foraminifera counts of sediment core PS1246-4 (GIK23246-4). 253 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23256-1 in the Arctic Ocean. 553 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 322 records from A revision of Malagasy species of Anochetus Mayr and Odontomachus Latreille (Hymenoptera: Formicidae).. 333 records from Distribution of calcareous foraminifers in sediment core Well 6407/7-2. 412 records from Benthic foraminifera counts of sediment core GIK23063-3. 936 records from Benthic foraminifera counts of sediment core PS1852-1 (GIK21852-1). 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 790 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_100MC. 329 records from Benthic foraminifera counts of sediment core GIK23351-1. 358 records from Counting of planktic foraminifera of ODP Hole 182-1129C. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 116 records from Abundance of dead benthic foraminifera in sediment core CD86_05_BC5. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 530 records from Benthic foraminifera counts of sediment core GIK23352-3. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 289 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 549 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 482 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 656 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_107MC. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) benthic foraminifera. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 3570 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 637 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 118 records from Abundance of dead benthic foraminifera in sediment core CD86_03_BC4. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 83 records from Abundance of living benthic foraminifera in sediment core CD86_02_BC5. 376 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 874 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_98MC. 2416 records from Upper Aptian Serre Chaitieu (Niveau Fallot) counts of benthic foraminifera, SE France. 477 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1242 records from Lower Albian Moriez core (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 745 records from Counts of the dead benthic foraminifera assemblage in surface sediments of the North Atlantic. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 127 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 66 records from Abundance of living benthic foraminifera in sediment core CD86_03_BC4. 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 21548 records from Benthic foraminifera abundance of ODP Site 184-1143. 345 records from Diversity of benthic foraminiferal faunas and benthic foraminifera accumulation rates of ODP Site 184-1143. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 1550 records from Species counts of benthic foraminifera of sediment core BOFS14K. 3492 records from Species counts of benthic foraminifera of sediment core BOFS5K. 38 records from Abundance of dead benthic foraminifera in sediment core CD86_07_BC4. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 129 records from Abundance of living benthic foraminifera in sediment core CD86_01_BC1. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 44245 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 79 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 62 records from Abundance of living benthic foraminifera in sediment core CD86_10_BC4. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, >150 µm. 18 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, >150 µm. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction 63-150 µm. 203945 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 57 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction 63-150 µm. 144 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction 63-150 µm. 274 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction >150 µm. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 11 records from Schmidt Museum of Natural History_Birds. 31 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction >150 µm. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 141 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 313 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction >150 µm. 2210 records from Merseyside BioBank - North Merseyside Mammals (unverified). 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 13 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 41 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC469. 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 4 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 30-63 µm fraction. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 7 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 30-63 µm fraction. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 140 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 516 records from (Appendix B1) Calcareous nannofossils of ODP Site 208-1262. 109 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB3708-1. 320 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD145_55802#4, 63-150 µm. 27 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, 63-150 µm. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 24 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, 63-150 µm. 23 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, 63-150 µm. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 134 records from Number of dead benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 67 records from Number of live benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 141 records from Assemblage of living benthic foraminifera in sediment core GeoB3702-2. 77 records from Faunal assemblage of sediment core GS7603-12. 73 records from Faunal assemblage of sediment core GS7603-13. 75 records from Faunal assemblage of sediment core TR149-32. 152 records from Faunal assemblage of sediment core TR149-38b. 891 records from Benthic foraminifera accumulation rate of sediment core MD01-2378 during marine isotope stage 3. 69 records from (Table T6) Calcareous nannofossil stratigraphy of ODP Hole 198-1210A. 13737 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 28 records from Counts of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 120 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 131 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm. 66 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, 63-150 µm. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 7765 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 248 records from Counts of Quaternary foraminifera of sediment core CRP-1 (App. 1). 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 190 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 267 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 166 records from Assemblage of living benthic foraminifera in sediment core GeoB3725-1. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB4912-4. 69 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 65 records from (Table 4b) Downcore distribution of live benthic foraminifera of sediment core SW_3b, California continental borderland. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 129 records from Assemblage of living benthic foraminifera in sediment core GeoB3705-2. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 142 records from Assemblage of living benthic foraminifera in sediment core GeoB4904-7. 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 588 records from (Table 5) Foraminiferal numbers of empty test of important species in surface sediments. 76 records from Faunal assemblage of sediment core GS7603-10. 148 records from Faunal assemblage of sediment core GS7603-11. 70 records from Faunal assemblage of sediment core GS7603-14. 89 records from Assemblage of living benthic foraminifera in sediment core GeoB4918-4. 347 records from (Table 4) Standing stock values of important species in surface sediments. 72 records from Faunal assemblage of sediment core TR149-35. 76 records from Faunal assemblage of sediment core TR149-37. 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 5438 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 915 records from (Appendix Table 2) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 6278 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 128 records from Total foraminifera counts from multinet M31/2_MSN895. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 215 records from Total foraminifera counts from multinet M31/3_MSN921. 233 records from Total foraminifera counts from multinet M32/5_MSN976. 76 records from Faunal assemblage of sediment core GS7603-8. 75 records from Faunal assemblage of sediment core GS7603-9. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 66 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 2381 records from Hawaiian Algal Database. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 165 records from Total foraminifera counts from multinet M31/3_MSN898. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 222 records from Total foraminifera counts from multinet M31/3_MSN910. 734 records from Stable oxygen isotope ratios of foraminifera from late middle Eocene sediments of ODP Site 171-1052 from Blake Plateau, West Atlantic Ocean (Appendix). 359 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 587 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from
Keywords: GBIF; biodiversity; species occurrences